Analisis Potensi Unggulan dan Daya Saing Sektor Pertanian dalam Pembangunan Daerah di Kabupaten Karangasem - NI PUTU PUTRIKA OKTARIANI; MADE ANTARA; I KETUT SUAMBA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2021)
Analysis of Superior Potential and Competitiveness of Agricultural Sector in Regional Development in Karangasem Regency The economic growth of Karangasem Regency has decreased between 2014 and 2019. The economic growth decline of Karangasem Regency is inseparable from the sectors that contribute to the economic growth of Karangasem Regency. The agricultural sector during 2014-2019 was the largest contributor to the Gross Regional Product (GRDP) of Karangasem Regency. The purpose of this study is to identify the magnitude of the role of the agricultural sector in regional development, identify leading sectors in Karangasem Regency and the development of the competitiveness of the agricultural sector in Karangasem Regency. This study use secondary data obtained from the Central Statistics Agency of Karangasem Regency and Bali Province. Descriptive statistical analysis technique is used to describe the role of the agricultural sector in regional development. Location Quotient Analysis (LQ) is used to analyze the superior potential of the Karangasem Regency agricultural sector, and Shift Share is used to determine the competitiveness of the agricultural sector and the growth of the Karangasem Regency. The analysis shows 1) the agricultural sector has a very big role in the formation of the Karangasem Regency GRDP, which was 24.61% in 2019 and was the sector that contributed the most. 2) the agriculture sector is a potential sector in Karangasem Regency. 3) the competitiveness of the agricultural sector falls into the slow category and its production could only meet the needs of the community. This research is expected to help the government in determining policies and increasing efforts in optimizing the agricultural sector because the agricultural sector has a very big role in society’s income and employment. In addition, the agricultural sector as the leading sector in Karangasem Regency shows slow competitiveness, so the government is expected to be able to improve facilities and develop programs to optimize the agricultural sector.